Penetapan Restitusi oleh LPSK dan Hakim Terhadap Korban Tindak Pidana Pornografi Berdasarkan Teori Keadilan - Kurniasari, Yunita; Yoserwan, Yoserwan; Mulyati, Nani (Faculty of Law, Andalas University, 2025)
Restitution is compensation given to victims or their families by perpetrators or third parties, covering both material losses and immaterial losses. This study explores how restitution serves justice for victims of pornography-related crimes and examines the influence of LPSK’s restitution valuation on judicial decisions at the Painan District Court. Using an empirical juridical method and interviews with judges and LPSK officers, the study found discrepancies between LPSK’s and the judge’s restitution assessments. While LPSK focused on the five reported suspects, the judge considered the possibility of other untried perpetrators, viewing full restitution from the five alone as unfair. Nevertheless, the judge still used LPSK’s decision as a reference. The study recommends that judges prioritize victim justice and consider shared liability mechanisms to ensure fair restitution without limiting victims’ rights to full recovery.